Faktor-faktor yang Mempengaruhi Keberhasilan Implementasi Penggunaan Presensi Online - DICKY PRAYOGA PRAYOGA; Elvira Mulya Nalien (JURNAL TERAPAN PEMERINTAHAN MINANGKABAU, 2023)
Government Regulation Number 94 of 2021 concerning Discipline for Civil Servants emphasizes that Civil Servants (PNS) are expected to be able to comply with obligations and avoid prohibitions specified in laws and regulations. One of them can be seen from the discipline for the time of arrival and return according to predetermined working hours. Therefore the Leadership Administration Bureau as one of the policy-making agencies intends to encourage civil servants to be more disciplined through online attendance application because they have noticed several forms of attendance disorder that are done manually. Thus the author intends to pay attention to and then describe the factors that influence the successful implementation of online attendance meant. The author uses a Qualitative Approach, Descriptive Method and data collection techniques in the form of Semi-Structured Interviews, Passive Participatory Observation and documentation. The informant determination technique is Purpossive Sampling namely the Head of Bureau as the policy maker and the operator as the technical implementer of online attendance at the Aceh Secretariat Leadership Administration Bureau. Meanwhile, data analysis techniques refer to Miles and Huberman, namely data reduction, data presentation and drawing conclusions. According to O'Brien and Marakas there are several factors that influence the successful implementation of an information system, namely the support of executive management, the involvement of end users(end user), the use of clear needs, clear planning and real expectations. Based on the results of writing, the use of online attendance of the Administration Bureau of the Aceh Secretariat Leadership is running well, judging from the goodness of all the dimensions referred to. All civil servants who work for these agencies have used the presence online application so as to coordinate discipline in order to maximize working hours for better performance.